Hypoxia-Induced LncRNA-MIR210HG Promotes Cancer Progression By Inhibiting HIF-1α Degradation in Ovarian Cancer - Liu, Ping; Huang, Huiqiong; Qi, Xiaorong; Bian, Ce; Cheng, Meng; Liu, Lili; Xue, Luqi; Zhao, Xia; Yi, Tao; Quan, Yi (Frontiers in Oncology, 2021)
LncRNA-MIR210HG plays crucial roles in the progression of diverse cancers. However, the expression and function of MIR210HG in ovarian cancer remains unclear. In the present study, we aimed to determine the expression and function of lncRNA-MIR210HG in ovarian cancer under hypoxic conditions. MIR210HG expression in ovarian cancer cells under hypoxic conditions was determined by qPCR analysis, and the distribution was determined by FISH and qPCR analysis based on cell nucleus and cytosol RNA extraction. Epithelial-Mesenchymal Transition (EMT) assay and human umbilical vein endothelial cell-based tube formation and migration assays were employed to determine the potential function of MIR210HG in vitro, followed by establishment of a subcutaneous tumor model in mice. The direct target of MIR210HG was determined by RNA pull-down and western blotting. Furthermore, the expression and clinical correlation of MIR210HG was determined based on malignant tissues from ovarian cancer patients. Our results indicated that MIR210HG was induced by hypoxia, which is HIF-1α dependent and mainly located in the cytosol of ovarian cancer cells. Knockdown of MIR210HG significantly inhibited EMT and tumor angiogenesis in vitro and impaired tumor growth in mice. Molecular investigations indicated that MIR210HG directly targets HIF-1α protein and inhibits VHL-dependent HIF-1α protein degradation in ovarian cancer. Further results demonstrated that MIR210HG was upregulated in ovarian cancer tissues and correlated with tumor progression and poor prognosis of ovarian cancer patients. Our study suggests that hypoxia-induced MIR210HG promotes cancer progression by inhibiting HIF-1α degradation in ovarian cancer, which could be a therapeutic target for ovarian cancer.